Juridical Analysis of Article 45 Paragraph 2 of Law Number 19 of 2016 Concerning Information and Electronic Transactions Against Gambling Crimes Among the Community Based on Social Control Theory - Surya Kuswanto; M. Arafat Hermana; Ferawati Royani (JURNAL HUKUM SEHASEN, 2023)
Gambling is a game where players bet to choose one option among several options where only one choice is correct and wins. The player who loses the bet will give his bet to the winner. Rules and bet amounts are determined before the game starts. Community disease in the form of gambling in 2021 as many as 198 cases have been revealed with 294 suspects. 612 Online Gambling Cases in 2022. This online gambling crime is very popular among young people and adults so that this crime is difficult to eradicate considering that access to technology is developing rapidly and provides the lure of wealth. Seeing the rise of gambling crime cases, the authors are interested in conducting this research, namely how to analyze Juridically Article 45 paragraph 2 of Law Number 19 of 2016 concerning Information and Electronic Transactions Against Gambling Crimes Among the Community Based on Social Control Theory. The theoretical framework is the rationale that explains from which angle a problem will be reviewed, namely the theory of social control and theory of law enforcement. The legal research methodology used is normative legal research or library research.The community is also required to cooperate with the government in addition to closing access to gambling websites, the community is also expected to be able to report this gambling activity which incidentally is not only done alone but can also be done together. Based on the theory of law enforcement, the activity of harmonizing the relationship of values ​​that is described in solid principles and attitudes as a series of final stages of value translation. To create, maintain and maintain social peace of life. This theory plays an important role in the emergence of a deterrent effect, so that strict punishment can set an example for the perpetrators of this gambling crime. According to the author, these things can provide a sense of justice for all Indonesian people.